Locus of control and investment in training - Marco Caliendo; Deborah A. Cobb-Clark; Helke Seitz; Arne Uhlendorff (Deutsches Institut für Wirtschaftsforschung (DIW), 2016)
This paper extends standard models of work-related training by explicitly incorporating workers' locus of control into the investment decision. Our model both differentiates between general and specific training and accounts for the role of workers and firms in training decisions. Workers with an internal locus of control are predicted to engage in more general training than are their external co-workers because their subjective expected investment returns are higher. In contrast, we expect little relationship between specific training and locus of control because training returns largely accrue to firms rather than workers. We then empirically test the predictions of our model using data from the German Socioeconomic Panel (SOEP). We find that, consistent with our model, locus of control is related to participation in general but not specific training. Moreover, we provide evidence that locus of control influences participation in general training through its effect on workers' expectations about future wage increases. Specifically, general training is associated with a much larger increase in the expected likelihood of receiving a future pay raise for those with an internal rather than external locus of control, while we do not find any relationship in the case of specific training. Actual post-training wages for those who receive general or specific training do not depend on locus of control.
Keywords: J24; C23; D84; 330; Human Capital Investment; On-the-job Training; Locus of Control; Wage Expectations